2020
DOI: 10.1108/mabr-01-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Port service quality (PSQ) and customer satisfaction: an exploratory study of container ports in Vietnam

Abstract: Purpose This study aims to investigate the concept of port service quality (PSQ) and examine its influence on customer satisfaction in the container port sector in Vietnam. Despite the importance of the maritime industry in which port is a critical sector in the national economy, there has been no research so far which examines what PSQ entails and how it affects customer satisfaction in the context of Vietnam. Design/methodology/approach Following a literature review, a conceptual model of PSQ and its influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Meanwhile, the correlation coefficients for primary variables, especially the ease of arranging competitively priced shipment and custom clearance along with quality of port, were highly positively correlated. Quality of port infrastructure is of high importance since it ensures the scheduled and on time shipment within expected time [45]. It also ensures the capability of custom clearance with the track ability and tractability of consignments.…”
Section: Principle Component Analysis (Pca)mentioning
confidence: 99%
“…Meanwhile, the correlation coefficients for primary variables, especially the ease of arranging competitively priced shipment and custom clearance along with quality of port, were highly positively correlated. Quality of port infrastructure is of high importance since it ensures the scheduled and on time shipment within expected time [45]. It also ensures the capability of custom clearance with the track ability and tractability of consignments.…”
Section: Principle Component Analysis (Pca)mentioning
confidence: 99%
“…Also, the results of research Cullinane and Song (2003) emphasizes the importance of capital attraction and efficiency indicators, but has not examined the service quality index. Instead, Thai (2016) and Phan et al (2021) research studies introduce service quality as one of the factors influencing the success of this industry. Based on this, the important routes (Figure 5) of the map were identified, based on which it is recommended to the decision makers of BUSHEHR CT to take the necessary measures (Figure 6) to improve the situation of important and effective factors affecting the interests of the CT.…”
Section: Discussionmentioning
confidence: 99%
“…Sakyi and Immurana (2021) have examined the experimental evidence to evaluate the effect of efficiency on the commercial balance of CTs and, by using the generalized method of moments estimation technique concluded that the efficiency of the CT in the commercial balance has affect in short and long periods, and managers must make appropriate policies to improve efficiency. Phan et al (2021) have examined the impact of port service quality, and their research results indicate the impact of improving service quality on customer satisfaction and, ultimately, its performance. Jeevan et al (2018) first obtained five categories of influential and low factors; then used multiple regressions to analyze the data.…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…As customer satisfaction is significantly associated with service quality (Phan et al, 2020;Sayareh et al, 2016;Thai, 2008;Yeo et al, 2015), resource allocation is key to improve the services. Availability of reliable equipment, adequate intermodal connections and skilled labour are vital for a port to be efficient in service delivery (World Bank, 2018).…”
Section: Container Terminal Resources Resource Bundling Strategies and Service Performancementioning
confidence: 99%